Structure and dynamics of lipid membranes interacting with antivirulence end-phosphorylated polyethylene glycol block copolymers. Issue 4 (18th December 2019) - Yu, Jing; Mao, Jun; Nagao, Michihiro; Bu, Wei; Lin, Binhua; Hong, Kunlun; Jiang, Zhang; Liu, Yun; Qian, Shuo; Tirrell, Matthew; Chen, Wei
Abstract : The structure and dynamics of lipid membranes in the presence of extracellular macromolecules are critical for cell membrane functions and many pharmaceutical applications. Abstract : The structure and dynamics of lipid membranes in the presence of extracellular macromolecules are critical for cell membrane functions and many pharmaceutical applications. The pathogen virulence-suppressing end-phosphorylated polyethylene glycol (PEG) triblock copolymer (Pi-ABAPEG ) markedly changes the interactions with lipid vesicle membranes and prevents PEG-induced vesicle phase separation in contrast to the unphosphorylated copolymer (ABAPEG ). Pi-ABAPEG weakly absorbs on the surface of lipid vesicle membranes and slightly changes the structure of 1, 2-dimyristoyl- sn-glycero -3-phosphocholine (DMPC ) unilamellar vesicles at 37 °C, as evidenced by small angle neutron scattering. X-ray reflectivity measurements confirm the weak adsorption of Pi-ABAPEG on DMPC monolayer, resulting in a more compact DMPC monolayer structure. Neutron spin-echo results show that the adsorption of Pi-ABAPEG on DMPC vesicle membranes increases the membrane bending modulus κ .